A centrifuge modelling study of the response of piled structures to tunnelling - Franza, Andrea; Marshall, Alec M. (American Society of Civil Engineers, 2018)
Tunnelling beneath piled structures may compromise the stability and serviceability of the structure. The assessment of potential structure damage is a problem being faced by engineers across the globe. This paper presents the outcomes of a series of geotechnical centrifuge experiments designed to simulate the effect of excavating a tunnel beneath piled structures. The stiffness and weight effects of piled structures are examined independently using aluminium plates of varying stiffness (`equivalent beam' approach) and the addition of weights supporteby aluminium piles. Greenfeld displacement patterns and results from pile loading tests are also provided. The variation of structure displacement profiles with plate stiffness, weight, and tunnel volume loss are used to illustrate the main effects of tunnel-pile interaction and the contribution of the superstructure to the global tunnel-pile-structure interaction. Results indicate that piles have a detrimental role in tunnel-structure interaction problems, whereas the superstructure stiffness and weight can, respectively, reduce and increase structure distor-tions and settlements. Finally, the potential for structural damage is evaluated by comparing structure and greenfield deflection ratios as well as resulting modification factors. The paper presents a unique set of results and insights which provide valuable guidance to engineers working across the ground and structural engineering disciplines.